2019
DOI: 10.1002/adma.201904639
|View full text |Cite
|
Sign up to set email alerts
|

Intra/Extracellular Lactic Acid Exhaustion for Synergistic Metabolic Therapy and Immunotherapy of Tumors

Abstract: Regulating the tumor microenvironment (TME) has been a promising strategy to improve antitumor therapy. Here, a red blood cell membrane (mRBC)‐camouflaged hollow MnO2 (HMnO2) catalytic nanosystem embedded with lactate oxidase (LOX) and a glycolysis inhibitor (denoted as PMLR) is constructed for intra/extracellular lactic acid exhaustion as well as synergistic metabolic therapy and immunotherapy of tumor. Benefiting from the long‐circulation property of the mRBC, the nanosystem can gradually accumulate in a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
228
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(230 citation statements)
references
References 47 publications
2
228
0
Order By: Relevance
“…Figure 3B shows that the mean particle size of PAMAM-PEG-EpDT3/pMEG3 NPs was 180±0.15 nm with a polydispersity of 0.236 and zeta potential 19.7±0.23 mV ( Figure 3C). The appropriate particle size and zeta potential ensure that the NPs are enriched in tumor tissues through the enhanced permeability and retention effect (EPR) effect and taken up by tumor cells [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3B shows that the mean particle size of PAMAM-PEG-EpDT3/pMEG3 NPs was 180±0.15 nm with a polydispersity of 0.236 and zeta potential 19.7±0.23 mV ( Figure 3C). The appropriate particle size and zeta potential ensure that the NPs are enriched in tumor tissues through the enhanced permeability and retention effect (EPR) effect and taken up by tumor cells [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, through the pentose phosphate pathway (PPP)a bypass of glycolysis-glucose can be transformed into nucleotide, which is essential for tumor cell proliferation (43). Excess lactic acid production, a glycolysis product, plays a pro-inflammatory and anti-immune role in human cancer (44,45). TLRs have been reported to control glycolysis in immune system cells (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that aerobic glycolysis in tumors constantly produces lactic acid, which provides energy for the tumor, and the increased lactic acid in the microenvironment could also affect the immunotherapy effect [43]. It has also been found that antitumor metabolism therapy combined with immunotherapy can effectively inhibit tumor growth [44]. To further explore the relationship between the glycolysis-related gene signature and immune cell in ltration and immune function, we rst analyzed the immune scores, stromal scores and ESTIMATE scores of patients in the high-risk subgroup and low-risk subgroup based on our gene signature.…”
Section: Discussionmentioning
confidence: 99%